Syngnathia Between the Palate and Mouth Floor, Cleft Palate, and Funnel Chest. Issue 8 (November 2016) - Wang, Xi-Qian; Zhang, Wen-Feng; Wang, Yong-Gong; Bu, Lin-Lin; Hou, Ming
Abstract : Abstract: Syngnathia is a rare malformation involving soft tissue and/or bony adhesions between the maxilla and mandible. Less than 40 patients have been reported in the literature. Here the authors report a 6-month-old infant diagnosed as syngnathia of the palate and mouth floor combined with cleft palate and funnel chest in the Department of Oral and Maxillofacial Surgery at Henan Provincial People's Hospital in January 2015. The authors discussed and evaluated the diagnostic and treatment difficulties on surgical and anesthetic procedure. There is no standard treatment protocol, but early treatment is necessary to improve airway functions and infant feeding, and to support proper nutrition for the growth of maxillofacial region.